2015
DOI: 10.5455/gulhane.172603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mandibular bone structure in sickle cell anaemia patients

Abstract: Orak hücreli anemi (OHA) ailesel kaynaklı hemoglobinopatidir. OHA ve osteomiyelit başlangıcına dair birçok radyografik bulgu vardır. Retrospektif olarak Konik Işınlı Bilgisayarlı Tomografi (KIBT) ile 10 hasta değerlendirildi. KIBT ile elde edilen DICOM verileri OHA hastalarında mandibular kemik yapıdaki değişimleri değerlendirmek üzere üçüncü bir yazılıma transfer edildi. Hastalarda kemik dansitesi, trabeküler kalınlık, trabeküler ayrılma, trabeküler sayı, fraktal boyut, kapalı por sayısı, kapalı por hacmi, ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The exams most used for FA were panoramic radiographs (34 articles), [10][11][12]15,16, periapical radiographs (21 articles), 2,5,45-63 and cone beam CT (CBCT) (15 articles). 1,[64][65][66][67][68][69][70][71][72][73][74][75][76][77] Bitewing radiography, 63,78-80 micro-CT, [81][82][83] ultrasound, 84,85 sialography, 18,86 and lateral cephalometric radiography 87 were also found in this review (Figure 4). The included studies showed different sample sizes.…”
Section: Study Characteristicsmentioning
confidence: 56%
See 1 more Smart Citation
“…The exams most used for FA were panoramic radiographs (34 articles), [10][11][12]15,16, periapical radiographs (21 articles), 2,5,45-63 and cone beam CT (CBCT) (15 articles). 1,[64][65][66][67][68][69][70][71][72][73][74][75][76][77] Bitewing radiography, 63,78-80 micro-CT, [81][82][83] ultrasound, 84,85 sialography, 18,86 and lateral cephalometric radiography 87 were also found in this review (Figure 4). The included studies showed different sample sizes.…”
Section: Study Characteristicsmentioning
confidence: 56%
“…The advent of CBCT has brought great advances in dentistry. This diagnostic method uses threedimensional imaging, a reliable tool for the evaluation and planning of dental implants, 65 investigation of sickle cell anaemia, 70 Type 2 diabetes mellitus, 74 temporomandibular osteoarthritis, 75 orthodontic tooth movement, 67 bone repair surgery, 76 impacted canines, 77 mid-palatal suture fusion, 71,73 and prediction of low BMD. 1,72 Similar to panoramic radiographs, FA on a CBCT slice can be helpful in the differentiation of groups of patients with low BMD.…”
Section: Discussionmentioning
confidence: 99%
“…13,[26][27][28] It appears that although FA has been employed to evaluate osseous changes in the jaws of patients with a variety of disorders affecting bone, no studies have been found regarding FA on the effects of CS on the mandible. Avsever et al 29 compared the FD values of sickle cell anemia patients and control groups and reported that the FD values in sickle cell anemia patients were significantly lower. Sindeaux et al 27 discovered that MCW and FD values were significantly smaller in osteoporotic patients compared with healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, Gupta et al [18] reported Class I, II, and III malocclusions in 44%, 55%, and 1% of the transfusion-dependent thalassemia patients, respectively, which was not in consistence with the healthy children malocclusion ratios. This result could be due to the fact that hemoglobinopathies are associated with extramedullary hematopoiesis, and bone marrow hyperplasia, leading to maxillary prominence and higher prevalence of Class II malocclusion [18,19]. In addition, there is evidence reported in many studies about the generalized growth retardation resulting in mandibular retrusion in these patients [20][21][22].…”
Section: Dhc Category Gradesmentioning
confidence: 99%